First or Second Biologic in Inflammatory Bowel Disease: Combination Therapy or Monotherapy?. Issue 9 (October 2021) - Aoun, Roni; Jabak, Suha; Mourad, Fadi H.; Francis, Fadi F.; Regueiro, Miguel; Hashash, Jana G.
Abstract : The therapeutic armamentarium for patients with inflammatory bowel disease has been expanding. Current guidelines make recommendations about whether patients who are biologic naive should be receiving biologic monotherapy or combination therapy, depending on the class of biologics. However, due to the limited available data, guidance to inform clinical practice for patients receiving their second or more biologic are lacking. We hereby review the available data about the use of biologic monotherapy or combination therapy with concomitant immunomodulator therapies in patients receiving their first as well as those receiving their second biologic.